(untitled) (Research, Society and Development, 2020)
Studies show the differences between the H1N1 virus and SARS-CoV-2, noting that in COVID-19 positive patients there is a non-productive cough, gastrointestinal symptoms and fatigue, while in the H1N1 virus infection, productive cough and fever occur. This study aims to compare the similarities and differences between infections by Influenza A (H1N1) and SARS-CoV-2 (COVID-19) associating these diseases with the Acute Respiratory Discomfort Syndrome (ARDS). It is a qualitative bibliographic review that is based on the production based on studies already published. There are some similarities between the symptoms and transmission of H1N1 and Coronavirus, and as a result, it is necessary to differentiate them and discuss the epidemiological impact caused. The transmission of viruses generally occurs through contact with droplets of saliva or mucus from infected patients, mainly through sneezing and coughing. SARS-CoV-2 has a higher transmission rate compared to the H1N1 virus. Asymptomatic cases can occur in COVID-19 infection, in H1N1 this does not happen. The H1N1 virus has treatments, and vaccine available, while in COVID-19 there is still no fully effective treatment and vaccine development is still underway. Although there are similarities in the two infections, COVID-19 has a higher lethality rate and a greater spread of the infection.